MORPHOLOGICAL VARIATION OF Cyrtophyllum fragrans (Roxb.) AMONG FOUR HABITAT TYPES IN JAMBI PROVINCE: A MULTIVARIATE APPROACH - Dinanty, Fawwaz; Hamzah; Farikhah, Anisatul; Nisya, Dian; Nahlunnisa, Hafizah; Anggi Safira, Doani (Jurnal Silva Samalas, 2026)
Cyrtophyllum fragrans (Roxb.) Don is a high-value hardwood tree whose population in Jambi Province is threatened by habitat fragmentation and land conversion, yet morphological data based on local populations remain unavailable. This study examined quantitative and qualitative morphological variation of C. fragrans from four locations in Jambi Province representing different ecological conditions, and identified phenotypic clustering patterns using a multivariate approach. Observations were conducted on 39 individual trees; quantitative characters included tree height (TH), diameter at breast height (DBH), leaf length (LL), leaf width (LW), and petiole length (PL), while qualitative characters included lamina shape, apex, base, and margin. Data were analyzed using Principal Component Analysis (PCA) and Hierarchical Clustering on Principal Components (HCPC) with Ward’s method and Euclidean distance. All five quantitative characters (TH, DBH, LL, LW, and PL) differed significantly among locations: leaf dimension characters (LL, LW, PL) responded most strongly to light intensity gradients, while tree size characters (TH, DBH) reflected cumulative growth history and habitat fragmentation effects. PCA identified two independent phenotypic gradients explaining 80.4% of total variance: PC1 (45.7%) captured the leaf dimension gradient as a plastic response to light intensity, and PC2 (34.7%) captured the tree size gradient recording long-term growth accumulation. HCPC produced four clusters with cross-site composition: K1 (small leaves, full sun), K2 (suppressed axial growth), K3 (very large DBH, cumulative growth), and K4 (large leaves, shaded). Qualitative leaf characters (simple opposite leaves, elliptic lamina, acuminate to caudate apex, cuneate base, entire margin, and pinnate venation) were consistent with the species description of C. fragrans across all four accessions and showed no meaningful variation among locations, confirming their stability as species-level taxonomic markers. Site ecological conditions, not geographic origin, were the primary determinant of morphological phenotype in C. fragrans, with implications for individual-based selection of mother trees in breeding programs rather than location-based selection.